2020
DOI: 10.13189/cea.2020.080409
|View full text |Cite
|
Sign up to set email alerts
|

Practical Solutions to Ensure the Schedule Management of Ho Chi Minh City Urban Railway Project in Vietnam: Survey of Expert's Opinions

Abstract: The development of the construction industry is considered to be a significant factor contributing to the economic growth of states and countries. However, many studies have shown that the quality of time and schedule management on civil and construction projects has generally been poor. Thus, it is essential to investigate factors that significantly affect the project schedule. This research aims to examine the practice of time management on a particular construction transport project in a developing country,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In urban railway projects in Vietnam, Tran et al (2020) identified 25 factors affecting implementation progress: including changing materials and construction procedures, problems in project management and administration, a weak and inexperienced project management team, and deferring decisions about changes in the contract. The results of the literature review indicate that there is a paucity of research on the factors that cause schedule delays in rail projects and that almost all of it was conducted in developing nations, such as India, Iran, Ethiopia, and Vietnam.…”
Section: Factors Affecting Schedule Delaysmentioning
confidence: 99%
See 2 more Smart Citations
“…In urban railway projects in Vietnam, Tran et al (2020) identified 25 factors affecting implementation progress: including changing materials and construction procedures, problems in project management and administration, a weak and inexperienced project management team, and deferring decisions about changes in the contract. The results of the literature review indicate that there is a paucity of research on the factors that cause schedule delays in rail projects and that almost all of it was conducted in developing nations, such as India, Iran, Ethiopia, and Vietnam.…”
Section: Factors Affecting Schedule Delaysmentioning
confidence: 99%
“…In urban railway projects in Vietnam, Tran et al. (2020) identified 25 factors affecting implementation progress: including changing materials and construction procedures, problems in project management and administration, a weak and inexperienced project management team, and deferring decisions about changes in the contract.…”
Section: Time and Cost Causation Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation